Advances in computer graphics : 36th Computer Graphics International Conference, CGI 2019, Calgary, AB, Canada, June 17-20, 2019, Proceedings /: 36th Computer Graphics International Conference, CGI 2019, Calgary, AB, Canada, June 17-20, 2019, Proceedings. (2019) - Unknown
No abstract available